Designing a Process Evaluation to Examine Mechanisms of Change in Return to Work Outcomes Following Participation in Occupational Rehabilitation: A Theory-Driven and Interactive Research Approach. (28th June 2018) - Gensby, Ulrik; Braathen, Tore Norendal; Jensen, Chris; Eftedal, Monica
Abstract : There is a growing consensus that professional action in occupational rehabilitation should be research-based, and that practice-based knowledge is needed to achieve contextual insight and new theoretical understanding. Few study design examples exist to help inform an evaluation plan and develop research-practice interactions to examine process complexity of targeted occupational rehabilitation programs. This study design article is a proposal on a theory-driven and interactive research methodology for a process evaluation of a pragmatic intervention trial, known as STAiR. The aim of the process evaluation is to examine the delivery and implementation of an inpatient and an outpatient occupational rehabilitation program, and explore active mechanisms pertaining to patient experiences of the return to work (RTW) process. Qualitative and interactive data collection methods will include (a) participant observation of program setting and activities; (b) participatory dialogue conferences with program providers to facilitate initial logic modelling; (d) individual patient interviews at program intake and follow up; and (d) focus groups with rehabilitation teams and external stakeholders. The qualitative data will be supplemented with description of program activities and patient questionnaires. Program logic modelling is suggested to inform a logic analysis of how expected RTW outcomes and delivery of program activities are aligned and how contextual characteristics may clarify differences in achieved RTW outcomes. The proposed process evaluation approach may inform future design discussions and theoretical understanding, and it is expected that the applied knowledge gained through this study may help rehabilitation professionals better navigate potential challenges in clinical evaluation efforts.